2000
DOI: 10.1890/0012-9658(2000)081[2241:ssewbw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Supply-Side Ecology Works Both Ways: The Link Between Benthic Adults, Fecundity, and Larval Recruits

Abstract: “Supply‐side” ecology recognizes the potential role that recruitment plays in the local population dynamics of open systems. Apart from the applied fisheries literature, the converse link between adults and the production of cohorts of recruits has received much less attention. We used a hierarchical sampling design to investigate the relationships between adult abundance, fecundity, and rates of larval recruitment by acroporid corals on 33 reefs in five sectors (250–400 km apart) stretching from north to sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
226
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 364 publications
(240 citation statements)
references
References 44 publications
(51 reference statements)
7
226
1
3
Order By: Relevance
“…Tracking large fluctuations in the numbers of recruits at a focal study area cannot resolve whether most larvae died or were transported to neighboring locales beyond this area of inference (Morgan 1995). In contrast, sampling over large spatial and long temporal scales has demonstrated that larval production and recruitment can be coupled (Robertson et al 1988;Hughes et al 2000) and oceanographic patterns can result in predictable spatial changes in populations and communities (Yoshioka 1982;Broitman et al 2008;Shanks et al 2010).…”
mentioning
confidence: 99%
“…Tracking large fluctuations in the numbers of recruits at a focal study area cannot resolve whether most larvae died or were transported to neighboring locales beyond this area of inference (Morgan 1995). In contrast, sampling over large spatial and long temporal scales has demonstrated that larval production and recruitment can be coupled (Robertson et al 1988;Hughes et al 2000) and oceanographic patterns can result in predictable spatial changes in populations and communities (Yoshioka 1982;Broitman et al 2008;Shanks et al 2010).…”
mentioning
confidence: 99%
“…First principles suggest why organisms in some places should produce more offspring than those in other places, e.g., due to genetic or environmental variation. Yet few empirical examples (3)(4)(5)(6)(7)(8) exist from marine populations of spatial variation in reproductive output at scales relevant to management (10s to 100s of kilometers). Moreover, marine population models for reserve design often include the assumption that the coastal ocean is a wellmixed and fairly uniform environment, where potential recruits to the adult populations are part of a global ''pool'' (9).…”
mentioning
confidence: 99%
“…However, at some broader geographic scale (within or beyond Casco Bay), mussel recruit and adult abundances must be connected, as Hughes et al (2000) showed for corals on the Great Barrier Reef; this indeed is the basis of metapopulation theory and standard stock-recruitment models.…”
Section: Spatial Decoupling Of Adult and Recruit Abundancesmentioning
confidence: 93%